2020
DOI: 10.1108/ijlm-12-2019-0366
|View full text |Cite
|
Sign up to set email alerts
|

Belt and road initiative (BRI) supply chain risks: propositions and model development

Abstract: PurposeBelt and road initiative (BRI) is a transcontinental endeavor strategically connecting supply chains (SCs) and economic infrastructures to ignite business activities and achieve trade benefits. However, the rising global SC failure costs and risks associated with this initiative (owing to unique geopolitical, economic and mega-connectivity involving over 70 countries) necessitate examining BRI SC risks. Yet, research on the subject remains limited, and the purpose of this paper is to address this gap in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Similar to Asian countries like Pakistan and Sri Lanka, European countries like Serbia, Montenegro, and Hungary are not able to repay the loans and this raises the question of sustainable financing (Hurley et al, 2019). Ram and Zhang (2020) found that payoff and ROI are very low and most of the projects have long payback periods (Yuan et al, 2019). Thus, it is proposed that:…”
Section: Cluster 2 (Red) Infrastructural Expansion and Political And ...mentioning
confidence: 99%
“…Similar to Asian countries like Pakistan and Sri Lanka, European countries like Serbia, Montenegro, and Hungary are not able to repay the loans and this raises the question of sustainable financing (Hurley et al, 2019). Ram and Zhang (2020) found that payoff and ROI are very low and most of the projects have long payback periods (Yuan et al, 2019). Thus, it is proposed that:…”
Section: Cluster 2 (Red) Infrastructural Expansion and Political And ...mentioning
confidence: 99%
“…The issue of risk related to supply chains is discussed in the publication focused on identification and proposal of a set of seven risk factors that drive the risks associated with the Belt and Road initiative. Supply Chain risk and Belt and Road initiative models help to build a theory of risk management in supply chains [16]. An interesting approach is presented by B. Nitsche [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Radanliev et al (2020) identified a dynamic and self-adapting SC system supported by Artificial Intelligence and Machine Learning (AI/ML) and real-time intelligence for predictive cyber risk analytics. Etemadi et al (2021) described using blockchain for robust cyber SC risk management (CSCRM) (Gourisetti et al, 2019;Pournader et al, 2019;Alazab, 2020;Dehghani et al, 2020;Ram and Zhang, 2020;Etemadi et al, 2021). Barata (2021) looked at the ongoing fourth revolution of SCs (4SC) and cyber risks due to the evolution of technology (Rodger and George, 2017;Kumar et al, 2018;Golmohammadi and Hassini, 2020;Ahmad et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%